2012
DOI: 10.1590/s1413-86702012000200012
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibilities of Cryptococcus species complex isolates from AIDS and non-AIDS patients in Southeast China

Abstract: Fluconazole, itraconazole, and flucytosine have excellent in vitro activity against all tested clinical Cryptococcus spp., and we also found a high rate of tolerance to amphotericin B (MICs ranging from 0.55-1 μg/mL). Furthermore, C. neoformans isolates from acquired immune deficiency syndrome (AIDS) patients were less susceptible to fluconazole and flucytosine than those from non-AIDS patients. These data suggest that use of amphotericin B may lead to tolerance or resistance of the pathogen over time. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
3
2
Order By: Relevance
“…Studies conducted in several parts of the world have shown low MIC 50 and MIC 90 values for fluconazole against C. neoformans VNI [43][44][45]. In this study, the MIC 50 and MIC 90 values for fluconazole were 4-8 mg/L; however, higher values (2-128 mg/L) have been reported for isolates of C. neoformans VNI [46].…”
Section: Discussioncontrasting
confidence: 58%
“…Studies conducted in several parts of the world have shown low MIC 50 and MIC 90 values for fluconazole against C. neoformans VNI [43][44][45]. In this study, the MIC 50 and MIC 90 values for fluconazole were 4-8 mg/L; however, higher values (2-128 mg/L) have been reported for isolates of C. neoformans VNI [46].…”
Section: Discussioncontrasting
confidence: 58%
“…High MIC values (≥64 μg/ml) have been reported for fluconazole against C. gattii ( Sar et al, 2004 ; Tay et al, 2006 ; Soares et al, 2008 ; Lia et al, 2012 ), in contrast to this study, where we determined MIC values of ≤ 16 μg/ml. It is worth mentioning that MIC ≥16 μg/ml is believed to be the resistance cutoff for fluconazole; this value was observed from a single C. gattii ( C. deuterogattii ) isolate in this study.…”
Section: Discussioncontrasting
confidence: 98%
“…Studies conducted previously have shown low MIC 50 and MIC 90 values for fluconazole against C. neoformans ( Datta et al, 2003 ; Tay et al, 2006 ; Lia et al, 2012 ). In this study, the MIC 50 and MIC 90 values for fluconazole were 2–4 μg/ml; however, higher MIC 50 and MIC 90 values (4–8 and 2–128 μg/ml) have been reported for C. neoformans isolates ( Sar et al, 2004 ; Favalessa et al, 2014 ).…”
Section: Discussionmentioning
confidence: 90%
“…Ergosterol is an essential element for several aspects of fungal physiology 8 , which makes difficult for the cell to produce mutations related to resistance 9 . Most strains of the main fungal pathogens for humans have the inhibition of growth in vitro when exposed to concentrations from 0.05 to 1.0 µg/mL 10 . It means that strains presenting the minimal inhibitory concentrations (MIC) above this interval are considered potentially resistant.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%